Comparative Study of Guaymas Basin Microbiomes: Cold Seeps vs. Hydrothermal Vents Sediments - Cruaud, Perrine; Vigneron, Adrien; Pignet, Patricia; Caprais, Jean-Claude; Lesongeur, Françoise; Toffin, Laurent; Godfroy, Anne; Cambon-Bonavita, Marie-Anne (Frontiers in Marine Science, 2017)
In the Guaymas Basin, the presence at a few tens of kilometers of cold seeps and hydrothermal vents coupled with comparable sedimentary settings and depths offer a unique opportunity to assess and compare the microbial community composition of these deep-sea ecosystems. The microbial diversity in sediments from three cold seep and two hydrothermal vent assemblages were investigated using high-throughput 16S rRNA-sequencing. Numerous bacterial and archaeal lineages were detected in both cold seep and hydrothermal vent sediments. Various potential organic matter degraders (e.g. Chloroflexi, Atribacteria, MBG-D) and methane and sulfur cycling related microorganisms (e.g. ANME and methanogenic lineages, sulfate-reducing lineages) were detected in both ecosystems. This suggests that analogous metabolic processes such as organic matter degradation and anaerobic methane oxidation coupled to sulfate reduction, were probably occurring in these two contrasted ecosystems. These highlighted "core microbiome" of the Guaymas Basin chemosynthetic ecosystems might therefore result from the combined presence of up-rising fluid emissions and high sedimentary rates of organic matter in the Basin. These results, coupled with the detailed ribotype analysis of major archaeal lineages (ANME-1, ANME-2 and MBG-D), also suggest a potential connectivity among deep-sea ecosystems of the Guaymas Basin likely due to the sedimentary context and the absence of physical border. However, thermophilic and hyperthermophilic lineages (e.g. : Thermodesulfobacteria, Desulfurococcales, etc.) were exclusively identified in hydrothermally impacted sediments highlighting the strong influence of temperature gradients and other hydrothermally-related factors such as thermogenic sulfate reduction and sulfide formation on microbial community composition.